1971
DOI: 10.1111/j.1476-5381.1971.tb07209.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dopamine on pancreatic secretion in the dog

Abstract: Summary1. Effects of L-dopa and dopamine on the secretion of pancreatic juice were investigated in preparations of the isolated blood-perfused canine pancreas.2. Dopamine (1-10 ,ug) given intra-arterially caused a profuse flow of juice.3. The secretory activity of dopamine (3 ,ug) was approximately equal to that of secretin (01 unit).4. L-Dopa (10-100 [Lg) given by a single intra-arterial injection was ineffective, but infusion at 100 ,ug/min for 10 min caused a marked increase of secretion after a delay of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
1

Year Published

1973
1973
1985
1985

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 5 publications
4
42
1
Order By: Relevance
“…Dopamine in doses of 1, 3 or 10 dig i.a. caused a prompt increase in the secretion of pancreatic juice, as reported previously (4).…”
supporting
confidence: 64%
See 3 more Smart Citations
“…Dopamine in doses of 1, 3 or 10 dig i.a. caused a prompt increase in the secretion of pancreatic juice, as reported previously (4).…”
supporting
confidence: 64%
“…Previously we reported that dopamine produced marked increases in the secretion of pancreatic juice in the dog (4,5). The responses to dopamine were modified by haloperidol, a dopamine receptor antagonist (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Polyethylene cannulae were inserted into the gastroduodenal and the splenic arteries through which the pancreas was perfused with the animal's own blood from the left femoral artery by means of a Harvard peristaltic pump (Model 500-1200). The details of the preparation were described in a previous paper (Hashimoto et al, 1971). All experiments were performed under constant pressure at 100 mmHg (1 mmHg-1.333 mbar).…”
Section: Methodsmentioning
confidence: 99%